tc+sc-td-sd=

Simple and best practice solution for tc+sc-td-sd= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for tc+sc-td-sd= equation:


Simplifying
tc + sc + -1td + -1sd = 0

Reorder the terms:
cs + ct + -1ds + -1dt = 0

Solving
cs + ct + -1ds + -1dt = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add 'ds' to each side of the equation.
cs + ct + -1ds + ds + -1dt = 0 + ds

Combine like terms: -1ds + ds = 0
cs + ct + 0 + -1dt = 0 + ds
cs + ct + -1dt = 0 + ds
Remove the zero:
cs + ct + -1dt = ds

Add 'dt' to each side of the equation.
cs + ct + -1dt + dt = ds + dt

Combine like terms: -1dt + dt = 0
cs + ct + 0 = ds + dt
cs + ct = ds + dt

Reorder the terms:
cs + ct + -1ds + -1dt = ds + -1ds + dt + -1dt

Combine like terms: ds + -1ds = 0
cs + ct + -1ds + -1dt = 0 + dt + -1dt
cs + ct + -1ds + -1dt = dt + -1dt

Combine like terms: dt + -1dt = 0
cs + ct + -1ds + -1dt = 0

The solution to this equation could not be determined.

See similar equations:

| -30+5k=-8(k+7) | | 2200=56x | | (a+2b)+3c=a+(2b+3c) | | -4x-3y=-5 | | 7b-5=2(2b-13) | | -7[x-3]=-14 | | -39-8p=3-6(p+7) | | 2t^3-6t^2+12=0 | | x+9+4x=16-5 | | 2+6n=-4(7-3n) | | 32-5m=5m-7(m-2) | | 9x-16x=19+3(11-x) | | x^2-3x=49 | | Y+b-3w=5w+7b | | 32-5m=5-7(m-2) | | -6[2x-3]+15=9 | | 2.9[x+3.7]=17.4 | | very-15=-27 | | -14+7x=1-(5-5x) | | 3+(5+(-5))=3+0 | | 3-10x+8x=19 | | -9d+7=-10d | | my-9=-13 | | -8b-15+6b=102 | | 64x+16x+216-342x= | | -40-5a=4a-8(5+8a) | | 5(c-3)-(5-c)=0 | | -3[x+5]=12 | | -j+10=-3j | | w-10=7.9 | | 25=35-3(5w-20) | | -3h+9=-2h |

Equations solver categories